In vitro characterization of antimicrobial efficacy and cytotoxicity of polyvinylpyrrolidone-iodine, N-acetylcysteine, methylglyoxal, and N-chlorotaurine as alternative antimicrobials in treating bovine clinical endometritis - Pas, Dijana; Oltmanns, Hilke; Meißner, Jessica (Frontiers in Veterinary Science, 2026)
Bovine clinical endometritis (CE) is a common indication for antibiotic use in dairy cows. The increase in bacterial resistance and the aspired decrease in antibiotic use under the One Health concept call for alternatives in treatment. Polyvinylpyrrolidone-iodine (PVP), N-acetylcysteine (NAC), methylglyoxal (MGO), and N-chlorotaurine (NCT) are known substances with antibacterial properties that could potentially serve as those alternatives. In a broth microdilution assay, their efficacy against the common cause of endometritis, Trueperella pyogenes, was investigated. By cytotoxicity testing on a primary bovine endometrial epithelial cell culture, potential adverse effects on cell proliferation, viability, and immune response (IL-6) were examined. While all four substances had an antibacterial effect on T. pyogenes, PVP, MGO, and NCT also showed cytotoxic effects. In contrast, NAC was tolerated well by the cells. In sum, the four tested substances can be considered potential alternatives to antibiotic treatments. Further research is, however, necessary to investigate their toxic effects in ex vivo or in vivo models and to identify effective dosages in animals.